Root responses to aluminium and iron stresses require the SIZ1 SUMO ligase to modulate the STOP1 transcription factor. (21st October 2021) - Mercier, Caroline; Roux, Brice; Have, Marien; Le Poder, Léa; Duong, Nathalie; David, Pascale; Leonhardt, Nathalie; Blanchard, Laurence; Naumann, Christin; Abel, Steffen; Cuyas, Laura; Pluchon, Sylvain; et al.
SUMMARY: STOP1, an Arabidopsis transcription factor favouring root growth tolerance against Al toxicity, acts in the response to iron under low Pi (−Pi). Previous studies have shown that Al and Fe regulate the stability and accumulation of STOP1 in roots, and that the STOP1 protein is sumoylated by an unknown E3 ligase. Here, using a forward genetics suppressor screen, we identified the E3 SUMO (small ubiquitin‐like modifier) ligase SIZ1 as a modulator of STOP1 signalling. Mutations in SIZ1 increase the expression of ALMT1 (a direct target of STOP1) and root growth responses to Al and Fe stress in a STOP1‐dependent manner. Moreover, loss‐of‐function mutations in SIZ1 enhance the abundance of STOP1 in the root tip. However, no sumoylated STOP1 protein was detected by Western blot analysis in our sumoylation assay in Escherichia coli, suggesting the presence of a more sophisticated mechanism. We conclude that the sumo ligase SIZ1 negatively regulates STOP1 signalling, at least in part by modulating STOP1 protein in the root tip. Our results will allow a better understanding of this signalling pathway. Significance Statement: The Arabidopsis transcription factor STOP1 allows Arabidopsis to respond to acidic, aluminium and iron rhizospheric stresses. The stability of the STOP1 protein is an important regulatory step involving post‐translational modifications by conjugation with ubiquitin. STOP1 is also subjected to sumoylation. In this work we identified the SUMO ligase SIZ1 as a modulator of STOP1 abundance and activity in the root tip.